Effects of Caffeine on Mood, Memory and Attention - Abdul Rafay Saleem, Rabia Iftikhar, Syed Messum Ali Kazmi, Ayesha Majeed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The Experimental study was carried out to investigate the effects of caffeine and caffeine withdrawal on mood, memory and mindful attention awareness of the students of Government College University, Lahore. Methodology: A total number of 24 participants aged between 18-26 years were recruited for the study from government college university among which there were 12 participants in the experimental and 12 participants in the control group. Furthermore, pretest and posttest equivalent group design was applied. Firstly, the standard progressive matrices (SPM) was used as a screening tool and then, to measure the effects of caffeine on attention awareness, memory and mood, the mindful attention awareness scale (MAAS), Wechsler memory scale (WMS) and brief mood introspection scale (BMIS) were applied. Results: The within group analysis was carried out by applying Friedman test which yielded the effects of caffeine and caffeine withdrawal on all the variables of the study. The lowest score of experimental group participants in posttest1 on these subscales indicates the impact of caffeine withdrawal while the score of participants on some subscales of these tests was not affected due to it. Conclusion: The findings of the experimental study helped to investigate the effects on caffeine and caffeine withdrawal on mood, memory and mindful attention awareness of university students. Most of the results of the present study were according to the results of researches that were conducted previously on caffeine but a few differed as well. The experimental study has implications for students, our society in general, researchers as well as for the parents of students. Keywords: Caffeine, withdrawal, effects, mood, memory and mindful attention awareness